The Influence of Taste, and Promotion Decisions to Purchase Indomie Instant Noodles - Nurlia, Titim; Sutrisno, Supadi Bambang; Sanjaya, Feri; Ristiana, Mela; Nafida, Nida (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
The aim of this research is to determine the partial and simultaneous influence of taste and sales promotion on purchasing decisions among Indomie instant noodle consumers in Tangerang Regency. In this study the sample size was 100 respondents. In this research, accidental sampling technique was used. The technique for collecting data uses a questionnaire that has been tested for validity and reliability. In this study the sample size was 100 respondents. Accidental sampling technique was used in this research. The data collection technique uses a questionnaire whose validity and reliability have been tested. This research uses analytical techniques in the form of multiple linear regression analysis. The results of the research conducted show that: (1) Cita Rasa has a positive and significant influence on the purchasing decisions of Indomie instant noodle consumers in Tangerang Regency, as evidenced by the coefficient (?1) = 0, > 0 on the Cita Rasa variable. (X1). t count 2.456 > t table 1.987 and significance (0.000) < 0.05. (2) Promotion has a positive and significant effect on the purchasing decisions of Indomie instant noodle consumers in Tangerang Regency, as evidenced by the offer variable (X2) with coefficient (?2) = 0, > 0. t count 2.456 > t table 1.987 and significance (0.000) < 0.05. The results of this analysis are expected to provide useful information for PT. Indofood Sukses Makmur develops flavors and promotions to increase consumer purchasing decisions for Indomie instant noodles.